Blood Pressure in Different Dementia Disorders, Mild Cognitive Impairment, and Subjective Cognitive Decline - Hestad, Knut; Engedal, Knut; Horndalsveen, Peter; Strand, Bjørn Heine (Frontiers in Aging Neuroscience, 2020)
The aim of the study was to investigate whether blood pressure (BP) differed among people with different dementia diagnoses, mild cognitive impairment, and subjective cognitive decline and whether BP differences were observed across age and gender. Our study population comprised clinical data from 6,236 patients (53.5% women) aged 45–97 years (mean 73.9, SD 9.6) referred to dementia assessment in 42 outpatient clinics across Norway during 2009–2019. Patients with the following diagnoses were included: Subjective cognitive decline (SCD), Mild cognitive impairment (MCI), dementia due to Alzheimer’s disease (AD), Vascular dementia (VaD), mixed AD and VaD, and dementia in Parkinson’s disease/Lewy body disease (PDD/LBD). For all diagnostic groups, SBP increased with age until about 80 years, after which it trended downward, whereas DBP declined after 60 years of age for all diagnostic groups. Patients aged 65 years and younger with SCD had lower SBP compared to AD patients at the same age, but SBP increased rapidly with increasing age, resulting in a substantially higher SBP at 80+ years compared with all other diagnostic groups. No other differences in SBP or diastolic blood pressure (DBP) were found among patients with the different dementia diagnosis. Neither SBP nor DBP differed between MCI and AD groups. An interaction between age and gender was found for SBP at younger ages, as women started out with a lower pressure than men did but ended up with higher SBP. Conclusion: Among 80+ patients, blood pressure did not differ as a function of the various dementia disorders. The SBP for the SCD patients of various age groups differed from all other diagnostic groups, indicating either that internal regulation of BP in older people is a risk factor for dementia or that brain damage causing dementia or MCI may led to changes in blood pressure. Brain aging seems to influence SBP differently in men and women.